SPECIFIC FEATURES OF MANAGEMENT IN SMALL BUSINESS ENTERPRISES : Maripova Shahlo Akramovna Doctoral candidate, Westminster International University in Tashkent, Republic of Uzbekistan maripovamaripova@gmail.com - Maripova, Shahlo (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Since the development of small business is approved as one of the strategic goals of the national economy of Republic of Uzbekistan, study of the small business management issues becomes relevant today. In this regard, our article aims to discuss the features of management specific for small businesses in order to study best practices that can enhance small business growth. The different works of various researchers and specialists are observed regarding the topic of the study. management methods for running of small entities are reviewed. During the study, both advantages and disadvantages of small business management are observed in detail. And the series of modern software products are offered for small businesses which aim at facilitating business processes.